Neon in carbon nanopores: wetting, growth mechanisms and cluster structures - Krainyukova, N.V. (Физика низких температур, 2007)
Low-temperature high-energy (50 keV) electron diffraction study of size-dependent structures and
growth mechanisms of neon samples in multiporous «amorphous» carbon films is presented. Electron
diffractograms were analyzed on the basis of the assumption that there exists the cluster size distribution in
deposits formed in substrate and multi-shell structures such as icosahedra, decahedra, fcc and hcp were
probed for different sizes up to approximately 3·10⁴ atoms. The analysis was based on the comparison of
precise experimental and calculated diffracted intensities with the help of the R (reliability) — factor
minimization procedure. Highly reproducible discrete distribution functions of sizes and structures were
found. The time-dependent evolution of diffractograms at earlier stages of growth was revealed. Initially
distinct diffraction peaks gradually «disappeared» although the total electron beam absorption evidenced
that deposited neon was preserved in the porous substrate. We ascribed this effect to diffusion-like gas penetration
from larger to smaller pores which resulted in a highly dispersed or even disordered substance. Evidently,
clusters initially grown during deposition were later soaked by a sponge-like substrate due to capillary
forces.